Tanggap Pertumbuhan dan Perkembangan Jagung Ketan terhadap Pemberian Amelioran dan Pupuk NPK pada Tanah Ultisol - Harini, Dini; Radian; Iwan Sasli (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2021)
The application of various types of organic matter as ameliorant and NPK fertilizer can increase the fertility of ultisol soil, physically and chemically. The study aimed to determine the effect of ameliorant types, the dose of NPK fertilizer and their interaction on the growth and development of glutinous corn on ultisol soil. The research was conducted in Bengkayang Regency, West Kalimantan from March to August 2020. The research used a factorial randomized block design. The first factor was the types of ameliorants with 5 levels, namely corncob biochar, corn waste bokashi, rice straw bokashi, cow manure, and chicken manure. The second factor was the dosage of NPK fertilizer with 4 levels, i.e., 100, 200, 300, and 400 kg ha-1. The chicken manure ameliorant increased plant height 2, 4, and 6 WAP (weeks after planting), ear diameter, ear length, ear weight per ear, and ear weight per plot. The best dose of NPK fertilizer for glutinous maize production is 200 kg ha-1 on ear length and weight per ear, and a dose of 100 kg ha-1 can stimulate plant growth based on plant height of 4 WAP. The combination of chicken manure and NPK fertilizer of 400 kg ha-1 produced the highest root dry weight, crown dry weight, and relative growth rate. Keywords: crop production, inorganic fertilizers, organic matter, soil fertility